EXPOSURE HISTORY OF THE ST-ROBERT (H5) FALL - Leya I.; Wieler R.; Aggrey K.; Herzog G.F.; Schnabel C.; Metzler K.; Hildebrand A.K.; Bouchards M.; Jull A.J.T.; Andrews H.R.; Wang M.-S.; Ferko T.E.; et al. (My University, 2001)
The compositionally typical H5 chondrite St-Robert has an exposure age, 7.8 Ma, indistinguishable from that of the main cluster of H chondrites. Small values of the cosmogenic 22Ne/21Ne ratio in interior samples imply a pre-atmospheric radius on the order of 40 cm. Sample depths based on tracks and the production rates of Bhattacharya et al. (1973) range from 6 to ∼40 cm and are generally larger than depths estimated from published 60Co activities, perhaps because the track production rates adopted are too high. Depth profiles of the production rates of 14C, 36Cl, 26Al, 10Be, and 21Ne in stony material show increases with depth and reach levels 5% to 15% higher than expected from modeling calculations. The maximum concentrations in St-Robert are, however, generally comparable to those measured for the L5 chondrite, Knyahinya, whose pre-atmospheric radius of ∼45 cm is thought to lead to the maximum possible production rates in chondrites. We infer that the pre-atmospheric radius of St-Robert was within 5 cm of the value that supports maximum production rates (i.e., 45 ± 5 cm). This radius corresponds to a pre-atmospheric mass of (1.3 ± 0.4) × 103 kg. The agreement of exposure ages for St-Robert obtained in several different ways and the similarity of the depth profiles for 14C, 26Al, 10Be, and 21Ne argue against a lengthy pre-exposure of St-Robert on the parent body and against a two-stage exposure after launch from the parent body. Following Morbidelli and Gladman (1998), we suggest that St-Robert was chipped from deep in its parent body, spent the next 7–8 Ma without undergoing a major collision, was nudged gradually into an orbital resonance with Jupiter, and then traveled quickly to Earth.